KAJIAN LABORATORIUM KARAKTERISTIK MARSHALL DAN KEPEKAAN ASPAL MODIFIKASI POLIMER TERHADAP KADAR ASPAL DITINJAU DARI PENGUJIAN DURABILITAS PADA CAMPURAN AC-BC - , Ferry Kurniawan, Prof. Ir. Suryo Hapsoro Tri Utomo, Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
In the last few years,the increasing of mechanical loading of vehicles and unpredictable weather make asphalt pavement performance, especially for durability, is reduced.That issue needs to be resolved. One of the solutions is the use of polymer modified bitumen. Asphalt used in this study is the bitumen pen 60/70, which has been given additive materials such as synthetic elastomeric polymer types. This study was conducted to determine the nature and characteristics of the sensitivity of Marshall asphalt content variation in the ACBC layer (Concrete-Asphalt Binder Course),which is reviewed from the level of durability (durability). In this study, a mixture of AC-BC is made using polymer modified asphalt. Analysis that is conducted on the mixtures is Marshall characteristics testing and durability. Sensitivity analysis in bitumen contentvariations, with long immersion time of the durability,is also conducted in the modified asphalt mixture. âOne way ANOVAâ statistical test is used for sensitivity analysis. Optimum bitument content (OBC) value can be obtained 6.5% in AC-BC mixtures using polymer modified asphalt. Value stability and MQ on polymer modified bitumen have tendency to decrease with increasing duration of soaking time, while the flow is increasing. The highest result of residual strength index analysis after 120 hours soaking time in OBC condition is 6,5%. IDP values in 5,5% and 6,5% of bitument content are almost the same and they are lower than IDP value in 7,5% of bitument content. IDK value in 5,5% of bitument content is 8,24003, in 6,5% of bitument content is 8,92547, and in 7,5% of bitument content is 6,12628. In the sensitivity analysis of polymer bitumen content variation (5.5%, 6.5%, and 7.5%) with the long soaking time (0.5, 24, 72, and 120 hours) toward Marshall Quotient values and durability, showed that there is an absence of sensitivity because all the values of Sig. are more than 0.05.